Species richness and folk therapeutic uses of ethnomedicinal plants in West Bengal, India - A meta-analysis - Vineeta; Gopal Shukla; Jahangeer A. Bhat; Sumit Chakravarty (Elsevier, 2022)
Background: West Bengal is a state rich in floral biodiversity, with a high occurrence of medicinal plants being used. The state is populated by several ethnic communities, which still rely on various ethnomedical practises. Unfortunately information relating to the medicinally useful species is not holistic or is fraganmentory. We thus felt for a meta-analysis and abridged the available information of the stateMethods: The purpose of the present study was to annotate the published information on ethnomedicinal plants used by various indigenous communities of West Bengal, India. We therefore searched the published Journal articles, book chapters, and scientific reports using Web of Science, Scopus, Google, Google Scholar, individual journal databases and personal communication to review the ethnomedicinal information of the state.Resutls: The meta-analysis resulted to a repository of 377 plant species represented by 99 families and 278 genera which were utilized for folk medicinal purposes. These ethnomedicinal plant species were used to treat a total of 126 different ailments and diseases. Stomach related problems were found common among the ethnic groups for which about half of the listed plant species were used for its treatment. Santal ethnic group was found richest with traditional knowledge related to folk medicinal purposes of 195 plant species. Some plant species Aerva lanata and Aristolochia indica were found commonly utilized by the communities. Leaves were prominently used plant part for folk therapies. Harvesting of the plants or their parts was largely unsustainable and is a matter of concern which needs urgent conservation action. Moreover, neglect and disregard to traditional culture and lores by the younger generation of the traditional communities is causing rapid decline and making the traditional knowledge system of these communities obsolete.Conclusion: Documentation of ethnomedicinal plant species and the associated traditional knowledge is vital for well being of future generation as well as their conservation. This meta-analysis will be useful as baseline information for research on new drug development which will give national and global recognition to the traditional knowledge system of these ethnic societies while, will boost their healthcare, ecological, socioeconomic and bio-cultural perspectives.